A triple whammy effect of employees' gender, job type, and service outcomes on consumer behavior. (October 2021) - Kim, Jong-Hyeong; Youn, Hyewon; Phau, Ian
Abstract: The extant literature reports inconsistent results regarding the effect of employee gender on customers' attitudes and behaviors. Furthermore, the previous research on congruency bias has mainly focused on female-dominant jobs. To address these issues, this study examined how customers' gender stereotypes affect their service evaluations and revisit intentions. Grounded in role congruity theory, congruency bias, and justification-suppression models, the results showed that employee gender and gender congruency with the norm for the job have differential impacts on customer evaluations. Furthermore, this study found asymmetric impacts of congruency bias on customer experiences. For example, customers showed lower satisfaction and revisit intention when female employees failed in a male-dominant job than when their male counterparts did. However, they showed equal levels of satisfaction and revisit intention when male and female employees failed in a female-dominant job. The results provide important insights into how to reduce customers' gender bias toward different gender-dominated jobs. Highlights: This study examined customers' gender stereotypes associated with hotel jobs. Congruency bias affects customer evaluations during negative service encounters. This study found asymmetric impacts of congruency bias on customer experiences.